2010
DOI: 10.1016/j.neurobiolaging.2008.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in glial cells of dopamine midbrain subregions in rhesus monkeys

Abstract: Aging remains the strongest risk factor for developing Parkinson's disease (PD), and there is selective vulnerability in midbrain DA neuron degeneration in PD. By tracking normal aging-related changes with an emphasis on regional specificity, factors involved in selective vulnerability and resistance to degeneration can be studied. Towards this end, we sought to determine whether age-related changes in microglia and astrocytes in rhesus monkeys are region-specific, suggestive of involvement in regional differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 68 publications
6
55
1
Order By: Relevance
“…Labeling was developed with Vector SG peroxidase substrate (SK-4700) to yield a dark blue reaction product in TauC3-immunopositive (TauC3+) neurons, and 0.05% 3,3′-diaminobenzidine (DAB; Sigma, D5637) containing 0.03% hydrogen peroxide to yield a reddish-brown reaction product in pS422-immunolabeled (pS422+) profiles. Tissue sections were slide mounted, and processed for Nissl counterstaining using Cresyl violet (Kanaan et al, 2010) to identify immunonegative nbM neurons and to aid in cytoarchitectonic analysis, and stored at 4 °C without cover-slipping prior to microdissection.…”
Section: Methodsmentioning
confidence: 99%
“…Labeling was developed with Vector SG peroxidase substrate (SK-4700) to yield a dark blue reaction product in TauC3-immunopositive (TauC3+) neurons, and 0.05% 3,3′-diaminobenzidine (DAB; Sigma, D5637) containing 0.03% hydrogen peroxide to yield a reddish-brown reaction product in pS422-immunolabeled (pS422+) profiles. Tissue sections were slide mounted, and processed for Nissl counterstaining using Cresyl violet (Kanaan et al, 2010) to identify immunonegative nbM neurons and to aid in cytoarchitectonic analysis, and stored at 4 °C without cover-slipping prior to microdissection.…”
Section: Methodsmentioning
confidence: 99%
“…The labeling was developed with 3,3 ′ -diaminobenzidine (Sigma, D5637), which produces a brown chromogen. Following IHC development, the sections were mounted and processed for Nissl counterstaining using the Cresyl violet protocol previously described (48). Control sections with the primary antibody omitted were performed to ensure the IHC signals were derived from tau antibody labeling and not due to nonspecific reactivity with the tissue (Supplementary Data 4, photomicrographs of primary delete control sections).…”
Section: Elisamentioning
confidence: 99%
“…Glial cells were identified using anti-GFAP or anti-HLA-DR antibodies, and tau inclusions were labeled with pS422. All staining for IF was done according to published methods (48, 49). For the colocalization of TNT1, TOC1, and pS422, the sections were incubated overnight at 4°C in a primary antibody solution containing each antibody followed by incubation in a secondary antibody solution of Alexa Fluor 488 goat anti-mouse IgG1-specific (A-21121), Alexa Fluor 568 goat anti-mouse IgM-specific (A-21043), and Alexa Fluor 405 goat anti-rabbit specific (A-31556) antibodies (all from Invitrogen, Billerica, MA, diluted 1:500) for 2 hours.…”
Section: Elisamentioning
confidence: 99%
“…There is also evidence for a higher cell loss in the VTA with aging (115). On the other hand, more recent and thorough studies in primates have provided support for the fact that PD represents an exaggerated version of aging by demonstrating accumulation of similar markers for dopaminergic neuron demise in both conditions (116)(117)(118)(119). To date, it is unknown whether different mechanisms are separating the two conditions, or whether idiopathic PD represents an acceleration of aging.…”
Section: Pathological Hallmarksmentioning
confidence: 99%
“…To date, it is unknown whether there are underlying differences between dopaminergic cell death in aging and PD or whether PD represents an accelerated version of aging. Although early studies pointed out a difference in the micro-anatomical pattern of dopaminergic cell loss within the SNpc (109,113,115,425), recent studies have demonstrated that markers of likely contributors to dopaminergic degeneration in PD accumulate with age in the SNpc, including α-synuclein and ubiquitin, markers of oxidative and nitrative stress, dopamine transporters and glial reactions (117)(118)(119), indicating that the underlying pathology is fundamentally the same. This hypothesis is supported by epidemiological studies, showing that age is by far the most prominent risk factor of PD with an exponential incidence rate with age (5,6).…”
Section: Selective Vulnerability Mediated By Aqp9mentioning
confidence: 99%